2017
DOI: 10.1016/j.dadm.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal thinning: Alzheimer's disease and aging

Abstract: IntroductionThe purpose of this study was to measure and to compare macular choroidal thickness (CT) between patients with mild Alzheimer's disease (AD), patients without AD, and elderly patients.MethodsCT was measured manually in 13 locations at 500-μm intervals of a horizontal and a vertical section from the fovea. Linear regression models were used to analyze the data.ResultsFifty patients with a diagnosis of mild AD (73.1 years), 152 patients without AD (71.03 years), and 50 elderly without AD (82.14 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 39 publications
4
52
0
1
Order By: Relevance
“…All these parameters presented a correlation with the disease stage (148). In the same way, a thinning of the choroid, measured by OCT, was also found (125,148,(151)(152)(153) (Table 1).…”
Section: Changes In the Early Ad And Their Prognostic Value In The Desupporting
confidence: 72%
“…All these parameters presented a correlation with the disease stage (148). In the same way, a thinning of the choroid, measured by OCT, was also found (125,148,(151)(152)(153) (Table 1).…”
Section: Changes In the Early Ad And Their Prognostic Value In The Desupporting
confidence: 72%
“…Notably, however, these prior live‐patient studies have been variable in their results. Bulut et al [22] found the choroid to be thinner temporally than nasally in AD, whereas Cunha et al [19] found the choroid to be thinner nasally than temporally. In addition, choroidal thickness changes in AD as measured in vivo have not correlated with patient psychometric scores [20,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Интерес к структурам хориоидеи обусловлен тем, что источником ее кровоснабжения, так же как и центральной артерии сетчатки, является внутренняя сонная артерия, питающая структуры головного мозга. Снижение толщины хориоидеи в макулярной зоне описано при болезни Альцгеймера [16,19] и Паркинсона [20], в то же время в перипапиллярной зоне при болезни Паркинсона отмечается утолщение хориоидеи [21]. Снижение толщины хориоидеи у пациентов с БГ во всех квадрантах макулярной зоны впервые описали С. Andrade и соавт.…”
Section: Discussionunclassified